Students’ Cognitive Strategies in Remembering English Vocabulary: Case Study at Ponpes NW Nurul Yaqien Sayang-Sayang Cakranegara Mataram - Tawali, Tawali; Suhaili, Muhamad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This research aimed to analyze the student’s cognitive strategies in remembering English Vocabulary survey study at Ponpes NW Nurul Yaqien Sayang-Sayang Cakranegara. The subject of this research was first grade VII-A of MTs NW Nurul Yaqien Sayang-Sayang in academic year 2023/2024. The subject of this study were 7 students. The method of this research was qualitative case study. The technique of data collection applied in this study were interview, recording and note taking/documents. Then the procedure of data analysis was data condensation, data display and conclusion drawing and verification used the theory of Miles and Huberman 2014. The result of this research, the researcher found out the types of student’s cognitive strategies in remembering English vocabulary. The strategies used by the students were Note taking strategy, repeating strategy, Grouping, Recombination, Imagery, Auditory representation, Keyword, Elaboration Transfer, and practice strategy. Therefore, the strategies used by students to remember the meaning and repetition strategy, translation strategy, and auditory representation and dominants used strategy note taking and repetition.